2015
DOI: 10.1039/c4ob01837k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of PS/PO-chimeric oligonucleotides using mixed oxathiaphospholane and phosphoramidite chemistry

Abstract: Chimeric oligonucleotides containing phosphodiester and phosphorothioate linkages have been obtained using the solid phase synthesis. The oligonucleotide parts possessing natural internucleotide phosphate bonds were assembled using commercially available nucleoside 3'-O-(2-cyanoethyl-N,N-diisopropylamino)phosphoramidites 7 whereas the phosphorothioate segment was built using nucleoside 3'-O-(2-thio-1,3,2-oxathiaphospholanes) 3. The oxidation steps, crucial for the conversion of phosphite linkages into the phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…39) (0.33 M in CH 3 CN, 30 min, room temperature). 40 In the present work, the 31 P NMR and MALDI-TOF MS measurements revealed that under these conditions the phosphoramidothioate linkage in DMT T NPS T OAc also remained unaffected (data not shown). The 9-nt DMT T PO (T PO ) 4 (T NPS ) 3 T-3 0 , was obtained in 42% yield as assessed from the DMT + cation assay.…”
Section: Attempts At Solid Phase Synthesis Of P-stereodened Nps-oligmentioning
confidence: 44%
“…39) (0.33 M in CH 3 CN, 30 min, room temperature). 40 In the present work, the 31 P NMR and MALDI-TOF MS measurements revealed that under these conditions the phosphoramidothioate linkage in DMT T NPS T OAc also remained unaffected (data not shown). The 9-nt DMT T PO (T PO ) 4 (T NPS ) 3 T-3 0 , was obtained in 42% yield as assessed from the DMT + cation assay.…”
Section: Attempts At Solid Phase Synthesis Of P-stereodened Nps-oligmentioning
confidence: 44%
“… 97 Similarly, since Ψ-based ASO synthesis does not use protecting groups on sulfur, it is not compatible with P(III)-based oxidative phosphodiester synthesis. 98 A P(V) approach to phosphodiester P(O) synthesis (Ψ O ) would be a fitting tribute to the origin of this field that commenced with but later abandoned P(V) due to low reactivity ( Figure 2 A). Finally, phosphorodithioates P(S) 2 are achiral linkages with reduced stereochemical complexity that maintain stability to nucleases are becoming increasingly common in this field.…”
Section: Putting It All Together: Chimeric Oligonucleotides Using a P(v)-platformmentioning
confidence: 99%
“…In contrast, P­(III) stereorandom ASO synthesis often leads to scalemic mixtures due to substrate bias rather than reagent control . Similarly, since Ψ-based ASO synthesis does not use protecting groups on sulfur, it is not compatible with P­(III)-based oxidative phosphodiester synthesis . A P­(V) approach to phosphodiester P­(O) synthesis (Ψ O ) would be a fitting tribute to the origin of this field that commenced with but later abandoned P­(V) due to low reactivity (Figure A).…”
Section: Putting It All Together: Chimeric Oligonucleotides Using a P...mentioning
confidence: 99%
“…Other reported applications include epoxidation of alkenes, Baeyer‐Villiger oxidation, adhesion promoters and intermediates in the synthesis of antitumour or antiparasitic drugs …”
Section: Introductionmentioning
confidence: 99%